The modular endoprosthesis for mandibular body replacement. Part 2: Finite element analysis of endoprosthesis reconstruction of the mandible - Wong, Raymond CW (CHURCHILL LIVINGSTONE, 2023)
10.1016/j.jcms.2012.03.010